Optimization of FDT Turmeric Rhizome Extract (Curcuma domestica Val.) Using a Combination of Crospovidone and Croscarmellose Sodium (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Turmeric rhizome (Curcuma domestica Val.) is a plant that has anti-diarrheal activity. To get an immediate effect and action in the treatment of diarrhea, turmeric rhizome is formulated into a fast-disintegrating tablet (FDT) dosage form. FDT is strongly influenced by super disintegrant (crushing material). Crospovidone is used as a super disintegrant, as it has a wicking effect (capillary action), while croscarmellose sodium has a swelling effect. The study aims to determine the effect of variations in the concentration of crospovidone and croscarmellose sodium on the physical properties of FDT and determine the optimal concentration of crospovidone and croscarmellose sodium. The sample used was a dry extract of turmeric rhizome. The dried extract of turmeric rhizome was made 5 runs with variations of crospovidone 2–5% and croscarmellose sodium 2–5%. Run 1 (2.75%: 4.25%), run 2 (3.5%: 3.5%), run 3 (5%: 2%), run 4 (2%: 5%), and run 5 (4.25%: 2.75%). The responses used included disintegration time, hardness, and restriction tests. The results utilized to determine the optimum formula were derived from the simplex lattice design (SLD) method. The outcomes of the optimal formula testing experiment were based on the findings from 13.0.5 predictive software experts, employing a one-sample t-test analysis at a 95% confidence level. The results of this study indicate that the combination of crospovidone and croscramellose sodium can reduce the response time of disintegration, hardness, and FDT. The optimum formula was obtained with the variation of crospovidone 3.5% and croscarmellose sodium 3.5%.